Decellularization of Wharton’s Jelly Increases Its Bioactivity and Antibacterial Properties - Dubus, M.; Scomazzon, L.; Chevrier, J.; Montanede, A.; Baldit, A.; Terryn, C.; Quilès, F.; Thomachot-Schneider, C.; Gangloff, S. C.; Bouland, N.; Gindraux, F.; Rammal, H.; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
The field of regenerative medicine has recently seen an emerging trend toward decellularized extracellular matrix (ECM) as a biological scaffold for stem cell-delivery. Human umbilical cord represents a valuable opportunity from both technical and ethical point of view to obtain allogenic ECM. Herein, we established a protocol, allowing the full removal of cell membranes and nuclei moieties from Wharton’s jelly (WJ) tissue. No alterations in the ECM components (i.e., collagen, GAG content, and growth factors), physical (i.e., porosity and swelling) and mechanical (i.e., linear tensile modulus) properties were noticed following WJ processing. Furthermore, no effect of the tissue processing on macromolecules and growth factors retention was observed, assuring thus a suitable bioactive matrix for cell maintenance upon recellularization. Based on the in vitro and in vivo biodegradability and stromal cell homing capabilities, decellularized WJ could provide an ideal substrate for stromal cells adhesion and colonization. Interestingly, the tissue processing increased the antibacterial and antiadhesive properties of WJ against Staphylococcus aureus and Staphylococcus epidermidis pathogens. Altogether, our results indicate that decellularized WJ matrix is able to limit Staphylococcus-related infections and to promote stromal cell homing, thus offering a versatile scaffold for tissue regenerative medicine.